IMPLEMENTASI PRINSIP AMAR MAKRUF NAHI MUNKAR SEBAGAI ETIKA POLITIK - Wardana, Dirga Arif; Paralian, Hotmatua; ., Yuzaidi (Jurnal Ushuluddin, 2023)
This thesis describes the implementation of the principle of Amar Ma’ruf Nahi Munkar as an Islamic political ethic. Amar Ma’ruf Nahi Munkar refers to efforts to achieve collective benefit, not solely for a particular group or community. This study aims to determine the extent to which the principle of Amar Ma’ruf Nahi Munkar is implemented as an Islamic political ethic. Islam teaches its followers to adhere to good ethics, with Amar Ma’ruf Nahi Munkar serving as a guiding principle. This research employs a qualitative method with a descriptive approach. The findings of this study reveal that Amar Ma’ruf Nahi Munkar is one of the fundamental teachings of Islam, commanded by Allah for Muslims to practice. To establish a strong and civilized Muslim society, a unifying principle is needed to guide individuals in performing good deeds and avoiding wrongdoing, ultimately achieving shared well-being. In this context, Amar Ma’ruf Nahi Munkar is the principle offered by Islam to build a robust and civilized society.